Discovering the relational goods: their nature, genesis and effects. Issue 2 (4th May 2019) - Donati, Pierpaolo
ABSTRACT: Two sociological mainstreams, one based on rational choice theory and one on relational sociology, converge in affirming that relational goods are those that can be enjoyed only if shared with some others. Both agree that it is a kind of goods different from strictly private goods, which are enjoyed alone, and from standard public goods, which are enjoyed impersonally by any number. However, they differ in the way they understand the nature of these goods, how they are generated and what are their social consequences. For the theory of rational choice, they derive from the fact that individuals find gratification in sharing a certain relationship with other people, so that the aggregation of these propensities generates a local public good. According to relational sociology, instead, these goods are emergent sui generis relationships that are sought for their intrinsic value, as bearers of good life for those who share them. The author compares these different approaches, highlighting their strengths and weaknesses. He concludes by claiming that relational goods have their own ontological status. They are produced by subjects who reflexively orient one towards the other to generate a relationship from which benefits derive for all those who participate in it.